Interpersonal coordination induce functional synergies through co-adaptation processes in team sports - Passos, P.; Araujo, D.; Travassos, B.; Vilar, L.; Duarte, R. (Complex systems in Sport, 2014)
The use of measures that capture coordination in different levels of team sports,such as geometrical centres, inter- and intrateam interpersonal distances, relative velocities and angles between opponent players, as well as the network analysis, have been increasingly used to describe and explain coordination between performers in sport. This chapter summarizes the developments in this area of work. It presents an overview of the conceptual and methodological developments in the recent study of interpersonal coordination in team sports. From the analysis of dyadic system interactions to the understanding of group behaviours in subunits of play, interactions within sport teams seem to assemble into functional synergies. The emergence of these functional grouping tendencies are governed by locally generated information sources from the relative positioning of other team players, motion directions and changes in motion, which attest the significant meaning of inter- and intrateam co-adaptation processes. The findings presented in this chapter might have some important implications concerning performance analysis, as well as for learning and training design.